An Attempt to Deal with The State of Women in Indian English Literature - Kaur, Komalpreet; Roy, Mamta (International Journal of Psychosocial Rehabilitation, 2020)
In this examination paper the essayist plays communicated the part of women and the identity of the female world that have been uncovered in the English literature. The paper has shown the development of women's attributes after the closure of the First World War. This was the time that women figured out how to emerge from their usual range of familiarity and they wanted to break their old generalized nature which was joined in them by the male man centric culture. Feminism in India goes for portraying, setting up and protecting equivalent political and social privileges similarly as equivalent entryways for Indian women. Feminism in Indian Fiction in English is, as typically considered, is a superb and ridiculous thought dealt with unobtrusively under restricted conditions. This article is an unassuming attempt to deal with the state of women in a man centric culture from the Vedic time frame to present day contemporary society. From one viewpoint, a lady is lauded to the statures of paradise by exemplifying her as a goddess, then again, she is cursed as an abla, a sissy who relies on individual for her reality and food.